Effect of microwave irradiation cycles on the pore structures and fractal dimension of coals with different ranks - Liankun Zhang; Zizheng Wang; Xiaoyu Zhang; Geng Li; Bo Yin; Xiaomin Liang; Rongrong Duan; Yuefang Wang (PLoS ONE, 2026)
A better understanding of the changes in the coal pore structure and the fractal dimension after microwave irradiation is beneficial for studying the reservoir stimulation and thus enhanced coal bed methane (ECBM) extraction. Place coal samples of three different ranks, namely subbituminous coal, bituminous coal, and anthracite coal, under microwave irradiation (2.45 GHz) for 1, 3, 5, and 10 cycles, respectively. Low temperature nitrogen gas adsorption (LT-N 2 GA) and mercury intrusion porosimetry (MIP) were employed to characterize pore structure changes before and after irradiation cycles quantitatively, and fractal theory was applied to analyze the overall roughness and irregularity index of pores. The results show that the overall type of pores in three kinds of coal samples does not change after microwave irradiation cycles modification, but only changes the pore volume distribution of the coal samples. The total pore volume of coal samples was increased by microwave irradiation cycles; The pore volume and specific surface area of micropores (<10 nm) decreased; The increase of pore volume and specific surface area of small pores (10–50 nm); The surface irregularities and irregularities in pore size distribution of micropores and small pores are reduced, and this phenomenon further weakens with the increase in the number of cycles. With more cycles of microwave irradiation, the pore volume of macropores (>50 nm) in coal increases, while their specific surface area decreases. After irradiation, the size distribution irregularity of macropores (50 nm-20 μm) is reduced, whereas that of macropores (>20 μm) is increased. Microwave irradiation cycles promote the development, expansion, and connectivity of coal sample pores and fractures, and make some micropores expand into small pores, which increases and enhances the connectivity of macroporous fractures.